REVIVING LEGACY: HOW DHABHLA WEAVING IS MAKING A COMEBACK - Mogha, Arooshi; Sharma, Neeraj Rawat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The globalization of trade has completed it easier for consumers to access a wide variety of clothing options from around the world. While this can create opportunities for handloom weavers to reach new markets, it also means they must compete with producers from other countries who may have lower production costs. However, the art of Dhabhla weaving from the arid landscapes of Kutch is an exception to the above fact as it experiences a revitalization, as artisans and enthusiasts alike seek to preserve and revive this ancient tradition weaving techniques.